Strategi Guru Bahasa Arab dalam Pembelajaran di Kelas Heterogen : (Studi Kasus Di Kelas Vii Madrasah Tsanawiyah Ma’had Al-Zaytun) - Rizky Ardiansyah Sarah Aulia; Moh. Mas’ud Arifin; Iis Susiawati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The teaching and learning process of Arabic in the madrasah environment plays a very important role. However, in practice, the diversity of students’ backgrounds, academic abilities, and learning styles poses unique challenges for teachers, especially in Grade VII of Madrasah Tsanawiyah Ma’had Al-Zaytun, which consists of heterogeneous classes. This study aims to describe the strategies employed by Arabic language teachers in managing heterogeneous classrooms and to identify supporting and inhibiting factors in implementing these strategies. This study employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results reveal that teachers apply various adaptive strategies such as interactive lectures, repetitive drills, the use of visual and audio media, grouping students based on ability, and emotional approaches through songs and stories. Supporting factors include teacher commitment, availability of learning media, and student enthusiasm, while inhibiting factors consist of limited preparation time, lack of training, and unequal foundational Arabic proficiency. These varied and inclusive strategies prove effective in helping students of different abilities engage optimally in the learning process.